Population density and urban air quality - Rainald Borck; Philipp Schrauth (Center for Economic Studies and ifo Institute (CESifo), 2019)
We use panel data from Germany to analyze the effect of population density on urban air pollution (nitrogen oxides, particulate matter and ozone). To address unobserved heterogeneity and omitted variables, we present long difference/fixed effects estimates and instrumental variables estimates, using historical population and soil quality as instruments. Our preferred estimates imply that a one-standard deviation increase in population density increases air pollution by 3-12%.
Keywords: Q53; R12; 330; population density; air pollution